2013
DOI: 10.1016/j.msec.2013.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effect of Si4+, Ca2+, and Mg2+ released from bioactive glasses on osteoblast osteocalcin expression and biomineralization

Abstract: a b s t r a c t a r t i c l e i n f o) after 30 days. In examining the extracellular matrix generated by cells when exposed to each GCM, it was found that 45S5 GCM had slightly elevated levels of mineral content within ECM as compared to 6P53-b GCM after 30 days while control treatments exhibited no mineral content. The formation of well-defined mineralized nodules (distinct PO 4 3− [960 cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…OPN, whose expression increases both in early differentiation and during mineralization, is known to be a middle-stage maker and be associated with the onset of ECM mineralization at a later point104950. OCN, being capable of binding ECM calcium to the developing bone matrix, is expressed at the later stages of bone matrix formation51 and the ECM deposition is closely regulated by OCN47. It is found here that the NC Ta surface remarkably out-performed the CG Ta surface in inducing higher mRNA expression of Col-I, OPN and OCN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…OPN, whose expression increases both in early differentiation and during mineralization, is known to be a middle-stage maker and be associated with the onset of ECM mineralization at a later point104950. OCN, being capable of binding ECM calcium to the developing bone matrix, is expressed at the later stages of bone matrix formation51 and the ECM deposition is closely regulated by OCN47. It is found here that the NC Ta surface remarkably out-performed the CG Ta surface in inducing higher mRNA expression of Col-I, OPN and OCN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also show that PDA-coated materials promote stem cell proliferation and differentiation [17,22,37]. At the last stages of bone matrix formation, OC is expressed and bound extracellular matrix Ca to the bone matrix development, and high serum levels are correlated with high bone mineral density [26,38]. Finally, we further evaluated Ca deposition on the PDA-coated PLA scaffolds for 14 days of cell culture in an osteogenic medium.…”
Section: Osteogenic Differentiationmentioning
confidence: 94%
“…A key to regenerative repair of bone is to: I) control the population of cells that are capable of entering into active phases of the cell cycle; II) complete the mitosis of cells with accurate replication of genes (cell proliferation); and III) achieve cellular differentiation into a phenotype capable of synthesizing a full complement of extracellular proteins that constitute a mature osteocyte [11][12][13] . B-G research deals in large part with developing a fundamental understanding of its dissolution and surface reactions, along with the tissue response to the dissolving material.…”
Section: Materials Properties Of B-g Mechanism Of Activity and Biolomentioning
confidence: 99%
“…It has been shown that new tissue is remodelled at a rate equal to that at which the glass dissolves: the longer is the dissolution, the better will be the deposition of bone tissue and growth 15) . References [11][12][13] summarize the sequence of biological events that comprise a cell cycle for a single osteoblast progenitor (adult stem) and its differentiation into mature osteocytes. These represent the cellular population responsible for extracellular matrix production and mineralization, the final step in bone development.…”
Section: Materials Properties Of B-g Mechanism Of Activity and Biolomentioning
confidence: 99%
See 1 more Smart Citation